Effects of physical properties on thermo-fluids cavitating flows. (November 2015) - Chen, T R; Wang, G Y; Huang, B; Li, D Q; Ma, X J; Li, X L
Abstract: The aims of this paper are to study the thermo-fluid cavitating flows and to evaluate the effects of physical properties on cavitation behaviours. The Favre-averaged Navier-Stokes equations with the energy equation are applied to numerically investigate the liquid nitrogen cavitating flows around a NASA hydrofoil. Meanwhile, the thermodynamic parameter Σ is used to assess the thermodynamic effects on cavitating flows. The results indicate that the thermodynamic effects on the thermo-fluid cavitating flows significantly affect the cavitation behaviours, including pressure and temperature distribution, the variation of physical properties, and cavity structures. The thermodynamic effects can be evaluated by physical properties under the same free-stream conditions. The global sensitivity analysis of liquid nitrogen suggests that ρv, Cl and L significantly influence temperature drop and cavity structure in the existing numerical framework, while pv plays the dominant role when these properties vary with temperature. The liquid viscosity μl slightly affects the flow structure via changing the Reynolds number Re equivalently, however, it hardly affects the temperature distribution.